ANALYSIS OF CUMULATIVE LIQUID CONTAMINANT CONTENT ACCUMULATED IN CNG TANK - Moch. Dwiyanto; D.A. Ismukurnianto; Yusep K. Caryana (Scientific Contributions Oil and Gas, 1999)
The utilization of natural gas as vehicles’ fuel (BBG) is now being developed in Indonesia for either private cars or public cars. The reasons of using BBG are (1) the price of BBG is lower than fuel oil (BBM), (2) the cost of BBG’s cars maintenance is lower than BBM’s cars maintenance, (3) BBG is an environmentally friendly fuel. Moreover, BBG’s infrastructure has been built in some big cities.